(S)TEM analysis of the interdiffusion and barrier layer formation in Mn/Cu heterostructures on SiO2 for interconnect technologies - Lozano, J; Lozano-Perez, S; Bogan, J; Wang, Y; Brennan, B; Nellist, P; Hughes, G (2012)
Mn/Cu heterostructures thermally evaporated onto SiO 2 and subsequently annealed were investigated by transmission electron microscopy (TEM) related techniques in order to study the diffusion interactions which lead to barrier layer formation. Electron energy loss spectroscopy provide evidence for the interdiffusion between the Mn and Cu layers following a 450 °C anneal, where the Mn diffuses towards the surface of the structure, while Cu diffuses towards the Mn/SiO 2, surrounding metallic Mn clusters but not propagating into the dielectric. The chemical composition of the 2-3 nm interfacial layer is primarily a mixture of +2 and +3 Mn valencies, in good agreement with previously reported results.